REBT GROUP COUNSELLING TO REDUCE STUDENTS' ACADEMIC PROCRASTINATION BEHAVIOUR - Wenny Audina Kartikasari; Neviyarni Neviyarni; Marjohan Marjohan; Afdal Afdal; Ifdil Ifdil (Jurnal Scientia, 2023)
This study aims to determine differences in the effectiveness of group services using a rational emotive behavior therapy approach in the experimental group and the provision of Prayitno group counseling services regarding academic procrastination behavior in the control group to reduce students' academic procrastination behavior. This study uses a quantitative method of experimental type. The sample consisted of 16 students and was selected using a proportional stratified random sampling technique. The instrument used is the Likert model scale. Statistical analysis of the data was performed using SPSS version 24. Significance was determined at the 0.05 level. Before the data was analyzed, the data was tested for variance, namely the Kolmogorov-Smirnov test (KS test) on the variable normality test and the covariance matrix equivalence test was carried out. There is an insignificant value (p <0.05) which indicates that the data is not significantly different from the normality of the multivariate variable, so that the parametric test can be applied. The results showed that: (1) There were significant differences in the experimental group students before and after attending group counseling with the rational emotive behavior therapy approach, (2) There were significant differences in the academic procrastination behavior of the control group. students before and after being given group counseling.